Mastering JavaScript - Fhala, Ben; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2015)
"Starting off with just some basic knowledge of JavaScript and HTML, this video will first lay a solid naming foundation for OOP coding by exploring the best naming conventions practices for primitive variables, constructors, methods, and properties. Then this video will shed some light on creating global namespace, create a pure JavaScript onload script, and walk through cross-browser compatibility. In this video you will learn how the onload and DOMContentLoaded events are actually triggered and understand how to use querySelectorAll method and dynamically load scripts using a script loader. As the course progresses, you will start building up our own libraries by integrating codes, methods, and logic, you will also expand your library with design patterns such as module, fa(cedil)cade, adapter, and singleton. Finally, you will create a working time manager and explore unit testing in JavaScript. After working through this video course, you will be equipped with all the knowledge, tips, and hacks you need to stand out in the advanced world of web development."--Resource description page.
Title from title screen (viewed October 2, 2015).
Date of publication taken from resource description page.
Presenter, Ben Fhala.
Keywords: JavaScript (Computer program language); HTML (Document markup language); Web site development; Electronic books